Methylene blue in the exploration of the bile ducts - Ruíz de Somocurcio Albareda, Jorge (1947)
In the study of the pathology of the biliary tract, is told in the clinic, with two aids to confirm or deny the suspicion of disease of the gallbladder. These methods are: the duodenal tubaje and cholecystography. Most authors agree that none of them is more important than the other and in a case that has clinically suspected gall stones or gall colesistisis, both tests should be performed, since the two ways of expelling gallbladder provide valuable data, in some cases being greater wealth of information cholecystography, but in others, and this most often, is the duodenal tubaje which give us more help.